EFFORTS TO CONTROL COMMUNITY STUNTING THROUGH THE ROLE OF COMMUNITY LEADERS AND RELIGIOUS LEADERS IN PAMEKASAN DISTRICT - Armita, Delizea; Hermawan, Hermawan; Hayat, Ainul (Erudio Journal of Educational Innovation, 2025)
Stunting is one of the most common chronic nutritional problems in children worldwide. The role and involvement of community leaders, including local leaders, religious leaders, and traditional leaders, have great significance in efforts to control stunting in Pamekasan Regency. This study reflects a systematic approach applied in conducting a literature review. The results of this study are Community leaders, such as local leaders, religious leaders, and traditional leaders, have a crucial role in efforts to control stunting in Pamekasan Regency. With their presence as social mobilizers, educators, motivators, and mediators, they are able to mobilize and organize the community in various activities aimed at improving children's nutrition and health.